2016
DOI: 10.1080/09589236.2016.1245605
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Masculinity Theory: overview, reflection and refinement

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
158
1
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 263 publications
(186 citation statements)
references
References 90 publications
13
158
1
14
Order By: Relevance
“…Subsequently, men are culturally compelled to perform certain overtly heterosexual behaviors and avoid engaging in those that would feminize them. Thus, one way of looking at homohysteria is to suggest that whereas homophobia limits the lives of homosexual men, homohysteria limits the lives of heterosexual men, too (Anderson and McCormack 2016).…”
Section: The Influence Of Homohysteria On Homosocialitymentioning
confidence: 99%
“…Subsequently, men are culturally compelled to perform certain overtly heterosexual behaviors and avoid engaging in those that would feminize them. Thus, one way of looking at homohysteria is to suggest that whereas homophobia limits the lives of homosexual men, homohysteria limits the lives of heterosexual men, too (Anderson and McCormack 2016).…”
Section: The Influence Of Homohysteria On Homosocialitymentioning
confidence: 99%
“…() who found that pornography consumers had more egalitarian attitudes than did nonconsumers, and Joseph and Black (:503) who concluded that “the commodification of sex is not inextricably linked to negative views of women.” They also support Garos et al. 's (:90) results suggesting that “pornography use may be motivated by other than misogynistic attitudes about women.” Indeed, using a “leisure framework” to study the effects of pornography helps researchers escape the “negative effects paradigm” and accounts for the centrality of leisure in late‐capitalist societies, including sexualized leisure (Anderson and McCormack ; Attwood and Smith ; Brents ; McCormack and Wignall ; McKee ; Smith et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, I theorized that men whom feared being perceived as gay, aligned their behaviours with anything socially coded as the 'opposite' in order to cast off suspicion from others that they might be gay. This, I argued, promoted both a binary of gender and sexuality, erasing bisexuality in the processes (Anderson & McCormack, 2016;Magrath, Cleland, & Anderson, 2017).…”
Section: Eric Andersonmentioning
confidence: 99%
“…The theory, further developed in conjunction with Mark McCormack (McCormack & Anderson, 2014a, 2014b and again two years later (Anderson & McCormack, 2016) is grounded in ample empirical evidence of young, mostly undergraduate men in both the United States and the United Kingdom. Here, we showed that the driving mechanism of inclusive masculinities was that straight male youth were inclusive of what used to be so taboo -homosexuality.…”
Section: Eric Andersonmentioning
confidence: 99%